The Effect of Providing Coleus amboinicus lour Ice Cream on Breast Milk Production - Deliana Br Karo; Nina Fitri; Wahyuni Wahyuni (Women, Midwives and Midwifery, 2023)
Background: Exclusive breastfeeding for six months is one of the global strategies to improve growth, development, health and survival of infants. However, the coverage of failing in providing exclusive breastfeeding are still high in many countries. Lactagogum is a substance that can increase milk production, lactagogum can be found in the Coleus amboinicus lour plant. Purpose: To identify the effect of providing Coleus amboinicus lour ice cream on breast milk production. Methods: This research employed an experimental study with a quasi-experimental research design and three group pre-test and post-test design on 15 respondents. The variables used are consuming Coleus amboinicus lour as the independent variable and milk production for the dependent variable. Statistical test using univariate and bivariate data analysis and Paired sample t test, using SPSS V. 26 Results: The results showed that 3 groups consisted of 15 respondents with the average breast milk production based on the baby’s weight of 3020 grams before consuming ice cream, 2940 grams after consuming 15 grams of ice cream, and 3040 grams after consuming 25 grams of ice cream. Besides, the frequency value of the baby’s weight after the treatment increased to 3051 grams, 3120 grams with 15 grams of ice cream, 3258 grams with 25 grams of ice cream. The Paired sample t-test obtained p = 0.0005 (p <0.05) and the independent t-test obtained a sig value of 0.015 and a sig. 0.008 (< 0.05) Conclusion: It can be concluded that there is an effect of giving Coleus amboinicus lour ice cream on the increase of breast milk production. It is suggested to provide Coleus amboinicus lour ice cream can be a solution in providing exclusive breastfeeding services for smooth breastfeeding.